Beyond The Classroom: Design Disruptors - Kansas State University, K-State First (Kansas State University. K-State First., 2016)
A poster promoting the presentation "Design Disruptors" at Kansas State University, hosted by Dr. Kim Baltrip, Assistant Professor in the A.Q. Miller School of Journalism and Mass Communications. The event was hosted on November 1, 2016 in Kedzie 004, and featured a screening of InVision's documentary that looked into renowned designers' worlds to see how design choices impact a viewer's daily life.
Keywords: Beyond The Classroom; Events; Engagement; Community building; Application of learning; Design disruptors; Posters